Pengujian Mekanik Serat Ijuk Pre Treatmeat NaOH Dengan Bahan Matriks Poliester - Josef Etheldreda Nana; Dominggus G. H. Adoe; Rima Nindia Selan (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2025)
In this increasingly developing era, the manufacturing industry is experiencing very rapid development. The need for materials in this field is also increasing. Materials with certain characteristics such as strength, toughness, and other mechanical properties according to needs are highly sought after. Composite is a material formed from a combination of two or more constituent materials through a non-homogeneous mixture, where the mechanical properties of each constituent material are different, the use of composite materials properly and efficiently requires extensive knowledge of their mechanical properties. While the use of ijuk is still limited to household needs, even exported in raw material conditions, therefore the use of ijuk as a basic material for composites is a new hope for utilizing ijuk into a commodity that has higher added value. The results of the study on the Testing of Ijuk Fiber Mechanics Pre Treatmeat Naoh With Polyester Matrix Material concluded that concentration affects the bending strength of 9.44 N / mm2 and deflection of 37.94 mm of ijuk fiber with the best results at a concentration with a soaking time of 60 minutes.